Bringing Sustainable Decisions in Organisations A focus on Bandar Raya Developments Berhad, Malaysia - Hyat, Ali Shan (2010)
This management project tries to analyse the word sustainability and its themes related to it. Sustainability is becoming an essential business practice amongst some of the world‟s leading corporations. The question is how far are companies willing to take the initiative to go green. What does green mean to them? Do they even understand the term „sustainability‟? Yes doing the right thing does make a lot of sense in a philosophical way but in reality there are cost-benefits related to the business world. This research paper first goes deep into the literature of sustainability, organisation culture and organisation structure, in order to understand their relationships with each other. My research is then followed by a methodology I adopt to analyse. Using the principles of grounded theory I adopt a narrative approach in analysing the management team of a development firm about their thoughts on sustainability and how we can bring about sustainable decisions in organisations. In order to validate my argument, over a period of few weeks I managed conduct semi-structured interviews with the top management of BRDB. Although the concluding thoughts maybe debatable keeping in mind the research limitations, after studying the literature available on this issue and its relations with organisation culture and structure and analysing the thoughts of a major development firm in Malaysia, I strongly suggest a culture change in order to bring about sustainable decisions in organisations.